Synthesis of a functionalized europium complex and deposition of luminescent Langmuir-Blodgett (LB) films - Adati, Renata Danielle [UNESP]; Pavinatto, Felippe J.; Monteiro, Jorge H. S. K. [UNESP]; Davolos, Marian Rosaly [UNESP]; Jafelicci, Miguel [UNESP]; Oliveira, Osvaldo N. (Royal Soc Chemistry, 2012)
The synthesis, characterization and formation of Langmuir-Blodgett (LB)films for the luminescent [(C12H25)(2)(CH3)(2)N][Eu(tta)(4)] complex, where [(C12H25)(2)(CH3)(2)](N+) is didodecyldimethylammonium and the tta ligand is thenoyltrifluoroacetone, are reported. The coordination of tta ligands to the Eu3+ ion was confirmed by FTIR spectroscopy and the emission spectrum comprised bands corresponding to D-5(0) -> F-7(0-4) transitions. The lifetime (tau) from the emission state (D-5(0))was 0.41 ms, measured by monitoring the hypersensitive D-5(0) -> F-7(2) transition, with the curve being fitted with a first-order exponential function. The surface pressure-area isotherm indicated that the anionic complex may form condensed structures at the air-water interface due to the amphiphilic properties of the counter ion and the beta-diketone ligand. Y-type LB films of [(C12H25)(2)(CH3)(2)N][Eu(tta)(4)] were deposited on quartz substrates, with preserved luminescence and a band assigned to the D-5(0) -> F-7(2) transition. The molecular arrangement at the air/water interface and the preserved luminescence in LB films are consistent with theoretical predictions using a semi-empirical Sparkle/AM1 calculation method for the molecule in vacuum. These tools were used for the first time to predict the behavior of organized films.